(untitled) (Eurasian Research Bulletin, 2023)
Being able to speak in the language being learnt is the greatest motivation a student can have and one of the most crucial elements in learning a language is motivation. Indeed, when learning becomes difficult, students who have a positive attitude about English are more likely to persevere and work hard. Looking into the importance of having positive attitude, the article discusses the reasons of low oral fluency in language learners and methods of its improvement.